Evaluación de la calidad de agua para consumo humano proveniente de la laguna La Toma en el distrito de Quiruvilca –La Libertad - Rodríguez Ventura, Gaby Magaly (2016)
Water is one of the most precious natural resources for the existence of every living being, guaranteeing the existence of plants, animals and humans; While it is considered of vital importance for human health with UN Security Counting and convenient supply of social hygiene and personal satisfaction. The objective of this research was to evaluate v Quality of water for human consumption from the lagoon La Toma in Quiruvilca District - La Libertad This sampled in three lagoon areas, reservoirs and urban areas during times of drought and precipitation of the samples tested was shown that there Presence of coliform bacteria type All sectors, with the Presence mayor in urban areas, so the quality index in times of drought and precipitation, ES Mayor 64, But despite the presence of bacteria the quality of drinking water from the lagoon La Toma Quiruvilca- in the District of La Libertad, is of acceptable quality for human consumption. Keywords: evaluation, water quality, coliforms.